A SHORT REVIEW ON AYURVEDIC APPROACH TOWARDS THE MAINTENANCE OF PERSONAL HYGIENE - Jadhav, Dnyaneshwar Kantaram; Bora, Rupesh Deelipkumar; Bawiskar, Sankalp Shyam (International Journal of Research -GRANTHAALAYAH, 2024)
Ayurveda not only a healing system but also it is a living style. So to protect the health and achieve the long life one should follow the some regiments describe in Ayurveda. That is daily regimens and seasonal regimens. During covid-19 whole world suffering from several illness that time only personal and social hygiene play major role. All these hygiene guidelines mentioned in Ayurveda. Personal guidelines mentioned under title of dincharya. In this review study will focus on Ayurvedic Approach towards the maintenance of personal hygiene.